А REGIONAL LINGUOCULTURAL COMPONENT OF TRAINING LANGUAGE TEACHER (CONTENTS, FORMS AND MEANS OF IMPLEMENTATION) - Nikitina, Tatiana; Rogaleva, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents the author’s concept of forming the regional cultural linguistic competence of language teachers in the process of study in pursuit of Bachelor's and Master's degrees. It regards the optimal structure and contents of the regional cultural linguistic competence, the forms and means of the implementation of the regional linguocultural component of teachers’professionaltraining. It shows different types of students’ in- and out-of-class activities and research projects connected with studying regional cultural linguistics, new models of modern means of teaching – the author’s textbooks and educational dictionaries that provide the implementation of the concept. The results of the methodical experiment that prove the effectiveness of the author’s model of forming the regional cultural linguistic competence of language teachers are given.